Choice of weapon sample based on fuzzy logic in defense management measures - Bilokur , Mykola; Sidorenko , Evgen; Khrebet, Valeriy; Gomola, Ivan; Hudyma, Viktor; Kopashynski, Sergii (Social Development and Security, 2020)
The possibility of improving the capability-based planning process is being investigated in order to minimize the need for weapons and military equipment and to maximize the acquisition of capabilities during their life cycle. Using the theory of fuzzy sets, the assessment of alternative samples of weapons and military equipment is carried out. A fuzzy inference model for determining the usefulness of weapons and military equipment in acquiring opportunities has been developed, based on fuzzy logic. The modeling of alternative models of weapons and military equipment was carried out in terms of costs at the stages of the life cycle “Use” and “Support” using the modern software environment MATLAB. The simulation results provided an opportunity at the planning stage to improve the efficiency of defense resource management using the value of the usefulness of weapons and military equipment. The introduction of the developed model into defense management makes it possible to automatically determine weapons and military equipment without the participation of experts, taking into account the cost of their life cycle and to bring the planning process closer to Euro-Atlantic approaches.